The Meaning and Methods of Drain of Wealth in Colonial India - Meena, Hareet Kumar (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
Among all the national movements in colonial countries, the Indian national movement (1885-1947) was the most deeply and firmly rooted in understanding the nature and character of colonial economic domination and exploitation. Its early leaders, known as the moderates, were the first in the 19th century to develop an economic critique of colonialism. The constant flow of wealth from erial return has been described by Indian nationalist and economists as drain of weaIndia to England for which India did not get an adequate economic, commercial or matlth from India. They made it clear that the colonial government was utilizing Indian resources, both natural and human, as land revenue, agriculture and industry not for developing India but for the industrial development and extension in Britain. The drain of wealth was interpreted as an indirect tribute extracted by imperial Britain from India year after year. According to the nationalist calculations, this chain amounted to one-half of the government revenues more than the entire land revenue collection and over one-third of Indiaâs total savings. The Drain of Wealth theory was systemically initiated by Dadabhai Naoroji in 1867 and further analyzed and developed by R. P. Dutt, M. G Ranade, etc. Their focal point of critique of colonialism was the drain theory. They pointed out that a large part of Indiaâs capital and wealth was being transferred or drained to Britain in the form of salaries and pensions of British civil and military officials working in India, interests on loans taken by the Indian government, profits of the British capitalists in India and the home charges or expenses of the Indian Government in Britain.Â